Potential use of pure and diluted choline chloride-based deep eutectic solvent in delignification of oil palm fronds - New, Eng Kein; Wu, Ta Yeong; Tien Loong Lee, Cornelius Basil; Poon, Zi Yet; Loow, Yu-Loong; Wei Foo, Luther Yang; Procentese, Alessandra; Siow, Lee Fong; Teoh, Wen Hui; Nik Daud, Nik Norsyahariati; Jahim, Jamaliah Md.; Mohammad, Abdul Wahab (Institution of Chemical Engineers, 2019)
The existence of deep eutectic solvents (DESs) has improved the process of biomass transformation and valorization due to its ability to break down the recalcitrant structure of biomass via delignification. However, the high viscosity of DES is one of the factors that restraints its effectiveness in delignification of biomass. The addition of water was expected to reduce the viscosity of DES and improve the process consequently. This study investigated the effects of water content in the DES (choline chloride:urea in 1:2 M ratio) on delignification of oil palm fronds (OPF), which are underutilized but available abundantly in Malaysia. The pretreatment was carried out at 120 °C for 4 h using DES at a solid-to-liquid ratio of 1:10 (w/v). In terms of lignin removal, 30 vol% of distilled water in DES was determined to achieve the optimal result at 16.31% in delignification of OPF. Delignification of OPF was further confirmed via a series of characterization tests. In comparison with pure DES, the aqueous DES enabled more favorable improvement of lignin removal in a biomass pretreatment. © 2018